How macroeconomic determinants influence the bank liquidity: The case of Serbia - Kalaš, Branimir; Mirović, Vera; Pavlović, Nataša (Industrija, 2024)
The objective of the research paper is to highlight the importance of macroeconomic framework to banking sector stability, as well as determine how selected macroeconomic determinants affect bank liquidity. The paper analyzes the influence of macroeconomic determinants on bank liquidity in Serbia from 2008 to 2022. Employing OLS model, the research discovered a significant influence of GDP growth rate, inflation, unemployment and gross savings, while gross government debt negatively affects bank liquidity, but without statistical significance. The obtained results indicate that a higher GDP growth rate and inflation rate lead to greater bank liquidity position, while a greater unemployment rate erodes the bank liquidity for the observed period. Likewise, a sufficient evel of gross savings enable positive influence on bank liquidity, while increased debt position has harmful effect on bank liquidity. These findings can be lucrative for bank managers, regulators, and economic policymakers during creating strategies, policies and procedures in terms of bank liquidity and stability.